Optimization of culture conditions for endophytic bacteria in mangrove plants and isolation and identification of bacteriocin - Jinju Peng; Xingpeng Xie; Tingli Fan; Haotian Ma; Yang Li; Shuaishuai Luo; Mengbo Yu; Yuexia Ding; Yi Ma (Frontiers Media S.A., 2024)
Introduction: The antibacterial protein PAG14 was extracted from a metabolite of Bacillus G14 isolated from mangrove plants.Methods: In this study, Pseudomonas aeruginosa, Pasteurell multocide, Enterobacter aerogenes, and Enterococcus faecalis were used as indicator bacteria to screen endophytes that exhibited antibacterial activity. The endophyte culture conditions were optimized to enhance productivity. Subsequently, the culture supernatant was salted using ammonium sulfate, followed by purification using dextran gel chromatography and ion exchange column techniques. Finally, the structures of antibacterial proteins were identified using mass spectrometry.Results and Discussion: The optimal culture conditions for Bacillus G14 were 2% mannitol, 0.5% fish peptone, 0.05% KH2PO4 + 0.05% K2HPO4 + 0.025% MnSO4·H2O. The antibacterial substances exhibited stability within the temperature range of 30-40°C and pH range of 5.0-7.0, while displaying sensitivity toward enzymes. The antibacterial activity decreased as the duration of UV irradiation increased. The antibacterial protein PAG14, isolated from the culture broth of Bacillus G14 through purification using dextran gel and ion-exchange columns, was identified as a class III bacteriocin using LC-MS/MS, similar to Lysozyme C. These findings serve as a theoretical foundation for the investigation and application of bacteriocins in food products.